A method for preparing P, N type liquid crystal elastomer based ionic thermoelectric fiber

By using liquid crystal elastomer as the substrate and crosslinking with ionic liquid, P and N type liquid crystal elastomer-based ionic thermoelectric fibers with high Seebeck coefficient and excellent tensile resilience performance were prepared, which solved the problem of insufficient performance of existing ionic thermoelectric materials and was suitable for the development of flexible wearable devices.

CN119265727BActive Publication Date: 2025-04-04DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411814109.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing ionic thermoelectric materials are based on plastic materials and are prepared in the form of thin films. The stretchability and resilience of the materials are limited, and the Seebeck coefficient is low, which cannot meet the needs of flexible wearable devices.

Method used

The liquid crystal elastomer is used as the substrate, and the ionic liquid crystal elastomer-based ionic thermoelectric fibers are prepared by soaking the ionic liquid solution and forming in combination with the mold method.

Benefits of technology

It significantly improves the Seebeck coefficient of ionic thermoelectric fibers and improves its tensile resilience performance, suitable for flexible wearable fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265727B_ABST
    Figure CN119265727B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a P, N type liquid crystal elastomer-based ionic thermoelectric fiber, wherein the ionic thermoelectric fiber is based on a liquid crystal elastomer and anions and cations of an ionic liquid as thermoelectric active materials, and a mold method and a solution immersion method are used to prepare a stretchable P, N type ionic thermoelectric fiber. The low-dimensional ionic thermoelectric fiber obtained by the present invention has the characteristics of being light, wearable, and stretchable and resilient, which promotes the practicality of ionic thermoelectric materials and has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermoelectric materials, and in particular relates to a method for preparing P, N type liquid crystal elastomer-based ionic thermoelectric fibers. Background Art

[0002] Energy and development have always been the core issues of modern society, and a large amount of heat energy from industry, nature and human body is an important resource that has been wasted and ignored. Thermoelectric conversion technology can directly convert low-level thermal energy into electrical energy and is regarded as an effective technology to solve the energy crisis. 2 Te 3 , PbTe and Si / Ge and other thermoelectric materials. Ionic thermoelectric materials have attracted extensive attention and research due to their ultra-high Seebeck coefficient, simple preparation process and green and pollution-free advantages.

[0003] At present, the research on ionic thermoelectric materials is mainly based on plastic materials such as PVA, PVDF and cellulose (Dan Z, Anna M, Andreas W, et al. Nature Communucations, 2019, 10:1093; Wu ZT, WangB X, Li J, et al. Nano Letters, 2022, 22(20):8152-8160). The prepared ionic thermoelectric materials are mainly in the form of thin films, and the stretchability and resilience of the materials are limited by the plastic substrate. Due to the technical difficulty, fiber-structured ionic thermoelectric materials are rarely reported. The only ionic thermoelectric fibers only use the thermocouple effect, resulting in the Seebeck coefficient of the material being only at the μV level and the mechanical properties cannot meet the needs of practical applications (Tian PD, Yi Z, Xiao QW, et al. Advanced Energy Materials, 2021, 11(44), 2102219). With the rapid development of the field of flexible wearables, ionic thermoelectric materials with a single film form and low thermoelectric performance are not conducive to the preparation, processing and application of flexible wearable devices. Therefore, the development of a new substrate, high-performance, stretchable and rebound low-dimensional ionic thermoelectric material is of great significance to the development of thermoelectric and wearable fields. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing P, N type liquid crystal elastomer-based ionic thermoelectric fibers, which overcomes the shortcomings of current ionic thermoelectrics that are mainly based on plastic materials and in the form of multiple thin films, and greatly improves the Seebeck coefficient and tensile resilience of the ionic thermoelectric fibers.

[0005] The present invention provides a method for preparing a liquid crystal elastomer-based ionic thermoelectric fiber, comprising:

[0006] (1) 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 2,2'-(ethylenedioxy)diethylmercaptan, pentaerythritol tetrakis-3-mercaptopropionate, and a solvent are mixed, stirred evenly, and then dipropylamine is added and stirred to obtain a liquid crystal elastomer solution;

[0007] (2) injecting the liquid crystal elastomer solution into the mold, allowing it to stand for molding, and peeling it off to obtain the liquid crystal elastomer fiber;

[0008] (3) Soaking the liquid crystal elastomer fiber in an ion liquid soaking solution to obtain a liquid crystal elastomer-based ionic thermoelectric fiber.

[0009] Preferably, in step (1), the molar ratio of 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 2,2'-(ethylenedioxy)diethylmercaptan and pentaerythritol tetrakis-3-mercaptopropionate is 1:1-3:0.01-0.05.

[0010] In the step (1), the solvent is ethyl acetate, and the volume ratio of dipropylamine to the solvent is 240-300:1.

[0011] Preferably, in step (1), the solvents are mixed and stirred, wherein the stirring parameters include: temperature of 65-80° C., time of 1-2 h, and stirring is magnetic stirring.

[0012] Preferably, dipropylamine is added in step (1) and stirred for 1 to 3 min.

[0013] Preferably, the standing in step (2) is horizontal standing for 10 to 15 hours.

[0014] The mold in step (2) is a mold tube, which includes but is not limited to polytetrafluoroethylene tubes and various glass material molds.

[0015] Preferably, the ionic liquid in step (3) is one or more of 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium dicyanamide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium dicyanamide, lithium tetrafluoroborate, and 1-butyl-3-methylimidazolium hexafluorophosphate. Among them, lithium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluorophosphate are N-type materials after impregnation, and the rest are P-type.

[0016] Preferably, the concentration of the ionic liquid soaking solution in step (3) is 0.5-5 mol / L; and the soaking time is 6-12 h.

[0017] The solvent of the ionic liquid soaking solution in step (3) is ethyl acetate, which specifically includes dissolving the ionic liquid in ethyl acetate and stirring to dissolve, thereby obtaining the ionic liquid soaking solution.

[0018] The invention provides a liquid crystal elastomer-based ionic thermoelectric fiber prepared by the method, wherein the fiber is a composite fiber material of liquid crystal elastomer and ionic liquid.

[0019] The fiber is obtained by taking a liquid crystal elastomer as a substrate and immersing and cross-linking with an ionic liquid at room temperature.

[0020] The ionic thermoelectric fiber uses liquid crystal elastomer as a base material, ionic liquid as a thermoelectric active material, and a mold method as a fiber forming method. The preparation of P and / or N-type liquid crystal elastomer-based ionic thermoelectric materials is achieved by a two-step method of forming liquid crystal elastomer fibers and then soaking them in ionic liquid solution.

[0021] The present invention provides an application of the liquid crystal elastomer-based ionic thermoelectric fiber or the liquid crystal elastomer-based ionic thermoelectric fiber prepared by the method in the field of ionic thermoelectricity and intelligent wearable devices.

[0022] The present invention uses liquid crystal elastomer as the substrate of ionic thermoelectric material, and successfully prepares a stable giant thermoelectric potential P, N type liquid crystal elastomer-based ionic thermoelectric fiber by soaking in ionic liquid solution. This method can not only make the liquid crystal elastomer fiber have ionic thermoelectric function, but also have excellent tensile resilience.

[0023] The present invention achieves the preparation of P and N type ionic thermoelectric fibers with good tensile resilience and thermoelectric properties based on liquid crystal elastomer by regulating the parameters of liquid crystal elastomer synthetic raw materials, the type, concentration and immersion time of ionic liquids, and the intermolecular interaction between anions and cations and liquid crystal elastomer molecular chains. This solves the problem that most of the current ionic thermoelectric materials are mainly in the form of thin films with limited use range, and the substrate is mainly made of plastic material with limited deformation capacity. The obtained low-dimensional ionic thermoelectric fibers have the characteristics of light weight, wearability, and tensile resilience, which promotes the practicality of ionic thermoelectric materials and has great application potential.

[0024] Beneficial Effects

[0025] (1) The invention provides a simple and practical method for preparing P and / or N-type liquid crystal elastomer-based ionic thermoelectric fibers. The method is simple to operate, has a short preparation cycle and stable effects, and is convenient for large-scale production.

[0026] (2) Compared with other ionic thermoelectric materials, the present invention adopts liquid crystal elastomer as the ionic thermoelectric material substrate. By soaking in ionic liquid solution, the anions, cations and liquid crystal elastomer molecular chains interact with each other. When the soaking time reaches 6 to 12 hours, the preparation of P and N type liquid crystal elastomer ionic thermoelectric fibers can be achieved. Compared with an ionic thermoelectric material disclosed in patent CN113571628A and a flexible ionic thermoelectric material disclosed in patent CN115895158A, the materials disclosed in the above patents have complicated preparation processes and poor tensile resilience. The preparation of the liquid crystal elastomer-based ionic thermoelectric fibers of the present invention greatly shortens the preparation time of ionic thermoelectric materials, optimizes the process, and has excellent tensile resilience. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The flow chart for the preparation of liquid crystal elastomer ionic thermoelectric fibers;

[0028] Figure 2 This is a graph of the Seebeck coefficient of the P-type liquid crystal elastomer ionic thermoelectric fiber / film immersed in different ionic liquid concentrations in Example 1;

[0029] Figure 3 This is a comparison chart of the Seebeck coefficients of the P-type liquid crystal elastomer ion thermoelectric fiber in Example 1 in the current thermoelectric fiber;

[0030] Figure 4 The Seebeck coefficient diagram of the P and N type liquid crystal elastomer ionic thermoelectric fibers at different immersion times in Example 2;

[0031] Figure 5 This is a physical picture of the liquid crystal elastomer-based ionic thermoelectric fiber in Example 2;

[0032] Figure 6 This is a real picture of the stretching and rebound test of the liquid crystal elastomer-based ionic thermoelectric fiber in Example 3. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] The main reagents used in the embodiments of the present invention: 1-ethyl-3-methylimidazole acetate was provided by Qingdao Olike New Material Technology Co., Ltd., lithium tetrafluoroborate was provided by Shanghai Yuanye Biotechnology Co., Ltd., liquid crystal elastomer synthesis raw material 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene was provided by Shanghai Bid Pharmaceutical Technology Co., Ltd., 2,2'-(ethylenedioxy)diethyl mercaptan and pentaerythritol tetrakis-3-mercaptopropionate were provided by Shanghai Titan Technology Co., Ltd., and none of them were subjected to other treatments.

[0035] Seebeck coefficient S i is based on the slope method, according to S i = -ΔV / ΔT The formula was measured using a self-built device, where the potential difference ΔV was generated by 8 temperature differences ΔT recorded by Keithley 2182 A. Each sample was tested 3 times and the average value was taken. The linear correlation between ΔV and ΔT (R 2 ) should be greater than 0.99.

[0036] Example 1

[0037] (1) Dissolve 2.389 g of 1,4-bis-[4-(3-acryloyloxypropoxy)benzoyloxy]-2-methylbenzene, 0.7 g of 2,2'-(ethylenedioxy)diethanethiol and 0.1 g of pentaerythritol tetrakis-3-mercaptopropionate in 2.4 ml of ethyl acetate, stir magnetically at 75 °C for 1 h, then add 9 μL of dipropylamine and stir for 1 min to obtain the product;

[0038] (2) injecting the product obtained in step (1) into a polytetrafluoroethylene tube and a glass culture dish respectively through a syringe, leaving it horizontally for 10 to 15 hours to allow it to form, and peeling it off to obtain a liquid crystal elastomer fiber and a liquid crystal elastomer film;

[0039] (3) dissolving 1-ethyl-3-methylimidazolium acetate in 5 mL of ethyl acetate and stirring for 30 min to obtain an ionic liquid soaking solution, wherein the concentration of 1-ethyl-3-methylimidazolium acetate in the ionic liquid soaking solution is 0.5-5 mol / L;

[0040] (4) The liquid crystal elastomer fiber and film formed in step (2) are respectively placed in the solution prepared in step (3) and immersed for 6 hours to obtain a P-type liquid crystal elastomer ionic thermoelectric material.

[0041] The laboratory built a Seebeck test system based on the slope method to test that the liquid crystal elastomer fiber prepared in this embodiment is P-type after being immersed in 1-ethyl-3-methylimidazolium acetate solution. When the concentration of 1-ethyl-3-methylimidazolium acetate is 1 mol / L and the immersion time is 6 h, the Seebeck coefficient is as high as 11.42 mV K-1 The liquid crystal elastomer film is P-type after being immersed in 1-ethyl-3-methylimidazolium acetate solution. When the concentration of 1-ethyl-3-methylimidazolium acetate is 1 mol / L and the immersion time is 6 h, the Seebeck coefficient is the highest at 6.56 mV K -1 .

[0042] The changes of the Seebeck coefficient of the P-type liquid crystal elastomer ionic thermoelectric fiber and film prepared in this embodiment with the concentration of the immersed ionic liquid were tested, and the results are as follows: Figure 2 As shown in the figure, when the concentration of 1-ethyl-3-methylimidazolium acetate is 1 M, the measured Seebeck coefficient of the P-type liquid crystal elastomer ionic thermoelectric fiber and film is the highest, and the performance of the liquid crystal elastomer fiber is far superior to that of the film, which is the highest performance of the P-type thermoelectric fiber at this stage. Figure 3 shown.

[0043] Example 2

[0044] (1) Dissolve 2.389 g of 1,4-bis-[4-(3-acryloyloxypropoxy)benzoyloxy]-2-methylbenzene, 0.7 g of 2,2'-(ethylenedioxy)diethanethiol and 0.1 g of pentaerythritol tetrakis-3-mercaptopropionate in 2.4 ml of ethyl acetate, stir magnetically at 75 °C for 1 h, then add 9 μL of dipropylamine and stir for 1 min to obtain the product;

[0045] (2) injecting the product obtained in step (1) into a polytetrafluoroethylene tube through a syringe, leaving it horizontally for 10 to 15 hours to allow it to form, and peeling it off to obtain liquid crystal elastomer fibers;

[0046] (3) dissolving 1-ethyl-3-methylimidazolium acetate or 1 mol / L lithium tetrafluoroborate in 5 mL of ethyl acetate and stirring for 30 min to obtain an ionic liquid soaking solution; wherein the ionic liquid soaking solution is an ionic liquid soaking solution with a 1-ethyl-3-methylimidazolium acetate concentration of 0.9 mol / L; or an ionic liquid soaking solution with a lithium tetrafluoroborate concentration of 1 mol / L;

[0047] (4) The liquid crystal elastomer fiber formed in step (2) is immersed in the solution prepared in step (3) for 6 hours to obtain P, N type liquid crystal elastomer ionic thermoelectric fibers.

[0048] The laboratory built a Seebeck test system based on the slope method to test that the liquid crystal elastomer fiber prepared in this embodiment is P-type after being immersed in 1-ethyl-3-methylimidazolium acetate solution. When the concentration of 1-ethyl-3-methylimidazolium acetate is 0.9 mol / L and the immersion time is 6 h, the Seebeck coefficient is 10.23 mV K -1After being immersed in lithium tetrafluoroborate solution, it is N-type. The concentration of lithium tetrafluoroborate is 1 mol / L. When the immersion time is 6 h, the Seebeck coefficient is -5.21 mV K -1 .

[0049] The Seebeck coefficient of the P and N type liquid crystal elastomer ionic thermoelectric fibers prepared in this embodiment was tested as a function of the immersion time in the ionic liquid. The results are shown in FIG. Figure 4 As shown in the figure, when the immersion time is 6 h, the measured Seebeck coefficient of the P and N type liquid crystal elastomer ionic thermoelectric fibers is the highest, which shows that the fibers reach adsorption saturation after immersion for 6 h.

[0050] Example 3

[0051] (1) Dissolve 2.389 g of 1,4-bis-[4-(3-acryloyloxypropoxy)benzoyloxy]-2-methylbenzene, 0.7 g of 2,2'-(ethylenedioxy)diethanethiol and 0.1 g of pentaerythritol tetrakis-3-mercaptopropionate in 2.4 ml of ethyl acetate, stir magnetically at 75 °C for 1 h, then add 9 μL of dipropylamine and stir for 1 min to obtain the product;

[0052] (2) injecting the product obtained in step (1) into a polytetrafluoroethylene tube through a syringe, leaving it horizontally for 10 to 15 hours to allow it to form, and peeling it off to obtain liquid crystal elastomer fibers;

[0053] (3) dissolving 1-ethyl-3-methylimidazolium acetate in 5 mL of ethyl acetate and stirring for 30 min to obtain an ionic liquid soaking solution, wherein the concentration of 1-ethyl-3-methylimidazolium acetate in the ionic liquid soaking solution is 0.7 mol / L;

[0054] (4) The liquid crystal elastomer fiber formed in step (2) is immersed in the solution prepared in step (3) for 6 hours to obtain a P-type liquid crystal elastomer ionic thermoelectric fiber.

[0055] The laboratory built a Seebeck test system based on the slope method to test that the liquid crystal elastomer fiber prepared in this embodiment is P-type after being immersed in 1-ethyl-3-methylimidazolium acetate solution. When the concentration of 1-ethyl-3-methylimidazolium acetate is 0.7 mol / L and the immersion time is 6 h, the Seebeck coefficient is 8.6 mV K -1 .

[0056] The tensile and resilience properties of the P-type liquid crystal elastomer-based ionic thermoelectric fibers prepared in this embodiment were tested, and the results are as follows: Figure 6 As shown, the initial fiber length is 2 cm, the maximum tensile strain can reach 100%, and it can rebound to the initial length, with good tensile resilience.

Claims

1. A method for preparing a liquid crystal elastomer-based ionic thermoelectric fiber, comprising: (1) 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 2,2'-(ethylenedioxy)diethylmercaptan, pentaerythritol tetrakis-3-mercaptopropionate, and a solvent are mixed and stirred, and then dipropylamine is added and stirred to obtain a liquid crystal elastomer solution; (2) injecting a liquid crystal elastomer solution into a mold, allowing it to stand for molding, and peeling it off to obtain a liquid crystal elastomer fiber; the mold is a mold tube; (3) Soaking the liquid crystal elastomer fiber in an ionic liquid soaking solution to obtain a liquid crystal elastomer-based ionic thermoelectric fiber; wherein the concentration of the ionic liquid soaking solution is 0.5-5 mol / L; and the soaking time is 6-12 h.

2. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, 2,2'-(ethylenedioxy)diethylmercaptan and pentaerythritol tetrakis-3-mercaptopropionate is 1:1-3:0.01-0.

05.

3. The preparation method according to claim 1, characterized in that: The solvent in step (1) is ethyl acetate; the volume ratio of dipropylamine to the solvent is 240-300:

1.

4. The preparation method according to claim 1, characterized in that: In step (1), the solvents are mixed and stirred, wherein the stirring parameters include: temperature of 65-80°C and time of 1-2 h; In the step (1), dipropylamine is added and stirred for 1 to 3 minutes.

5. The preparation method according to claim 1, characterized in that: The standing still in step (2) is horizontal standing still, and the time is 10 to 15 hours.

6. The preparation method according to claim 1, characterized in that: In the step (3), the ionic liquid is one or more of 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium dicyanamide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium dicyanamide, lithium tetrafluoroborate, and 1-butyl-3-methylimidazolium hexafluorophosphate.

7. The preparation method according to claim 1, characterized in that: The solvent in the ionic liquid soaking solution in step (3) is ethyl acetate.

8. A liquid crystal elastomer-based ionic thermoelectric fiber prepared by the method of claim 1.

9. An application of the liquid crystal elastomer-based ionic thermoelectric fiber according to claim 8 in the fields of ionic thermoelectricity and smart wearables.